(untitled) (American Journal of Islam and Society, 2014)
On March 21, 2014, Seyed Amir Akrami, a visiting Iranian scholar at the Eastern Mennonite University in Harrisonburg, VA, visited the headquarters of the International Institute of Islamic Thought. He holds a PhD in the philosophy of religion (McGill University), as well as a BA and an MA in Islamic theology and mysticism (University of Tehran). In his opening remarks he stated that with the end of the Cold War, the closer relations between politics and religion necessitates interfaith relations. Realizing this, the West (especially the United States) has undertaken an unprecedented step: establishing centers for religion and diplomacy. Akrami considers this a very positive development. Another reason for this new approach was Samuel Huntington’s (d. 2008) “clash of civilizations” theory, which upset many Muslims. What is often forgotten, however, is that Huntington also called for dialogue. President Mohammad Khatami of Iran responded to this by launching his 2001 “dialogue of civilizations” initiative. Akrami maintains that political and economic polarization is being replaced by cultures, of which religion is a very important part. Given that Islam and Christianity are the world’s two largest religions, it is more practical to focus on them than trying to start a dialogue with all religions at this time. The second part of his presentation consisted of several historical observations related to Christian views of Islam, Muslim views of other religions (especially Christianity), and how best to approach/view these two religions’ relationship. John of Damascus (d. 750), an early Christian scholar of Islam noted for his largely polemical works, viewed Islam as a Christian heresy. Centuries later, the Crusades poisoned Muslim-Christian relations. But, importantly, part of the reason for this military onslaught was the great schism of 1054 that split Christendom between the Catholic Church (Rome) and the Orthodox Church (Constantinople). Normal Daniel’s Islam and the West: The Making of an Image (Oxford: Oneworld, 1993) is a very good source for these negative views. Among them are the following: (1) Muhammad was a cardinal who wanted to become the pope. When he failed in this attempt, he became a heretic; (2) Muhammad trained a dove or a bird to sit on his shoulder in order to deceive/delude his followers into thinking that he was being inspired; and (3) Dante, in his Divine Comedy, called Muhammad an imposter and liar and therefore placed him in the eighth circle of hell ...